1999
DOI: 10.1148/radiology.210.2.r99fe13443
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Nodules in Budd-Chiari Syndrome: Imaging Features

Abstract: In patients with chronic Budd-Chiari syndrome, multiple (> 10) small (< 4-cm) lesions are suggestive of benignity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 18 publications
10
99
2
5
Order By: Relevance
“…In agreement with previous studies that have analyzed FNHlesions in patients with other vascular diseases, such as BuddChiari syndrome or congenital portosystemic shunt [9][10][11][12][13][14], we found that two imaging findings are the most common and distinctive features of FNH-like lesions. First, all lesions demonstrated intense and homogeneous contrast enhance- Corresponding gadolinium-enhanced, fat-suppressed T1-weighted 3D GRE images (212 ms/4 ms; 80°) show lesion's intense and homogeneous hyperintensity during the hepatic arterial dominant phase (c), which gradually fades to near isointensity compared with the background liver during the interstitial phase (d).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous studies that have analyzed FNHlesions in patients with other vascular diseases, such as BuddChiari syndrome or congenital portosystemic shunt [9][10][11][12][13][14], we found that two imaging findings are the most common and distinctive features of FNH-like lesions. First, all lesions demonstrated intense and homogeneous contrast enhance- Corresponding gadolinium-enhanced, fat-suppressed T1-weighted 3D GRE images (212 ms/4 ms; 80°) show lesion's intense and homogeneous hyperintensity during the hepatic arterial dominant phase (c), which gradually fades to near isointensity compared with the background liver during the interstitial phase (d).…”
Section: Discussionsupporting
confidence: 92%
“…Although rare, CTPV can profoundly alter liver morphology and vascular haemodynamics, mimicking other hepatic disorders (most notably cirrhosis) [2][3][4][5][6]. In addition, recent anecdotal observations suggest that CTPV might foster the growth of hypervascular liver nodules with histological features and pathogenesis similar to that of focal nodular hyperplasialike (FNH-like) lesions found in other vascular disorders of the liver (e.g., Budd-Chiari syndrome, hereditary hemorrhagic telangectasia, congenital portosystemic shunt, and congenital hepatic fibrosis [7][8][9][10][11][12][13][14]). These lesions represent a benign hyperplasia of the hepatic parenchyma in response to increased arterial perfusion in areas with reduced or absent portal blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Review of literature showed that benign nodules in Budd Chiari syndrome can show increased T2 signal intensity. 24 Central area altered signal intensity which is hypointense on T1 weighted images and hyperintense on T2 weighted images is noted in many nodules in this patient which corresponds with central scarring. In a study by Maetani et al of 15 lesions larger than 1 cm in diameter, a central scar was found in six nodules.…”
Section: Lesion Characterizationmentioning
confidence: 61%
“…3D CE MRA found 2 patients with primary BCS developed HCC during a long-term follow-up period. The development of HCC in patients with chronic BCS has been reported in the literature [29] . According to that report, many factors, such as chronic viral infection or cirrhosis might play a role in the development of this malignancy.…”
Section: Discussionmentioning
confidence: 98%